2014
DOI: 10.1111/jep.12201
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported adherence by MARSCZ reflects LDL cholesterol goal achievement among statin users: validation study in the Czech Republic

Abstract: This study proved MARS-CZ as an acceptable self-reported adherence measure. In routine clinical practice, MARS-CZ could be helpful to reveal medication non-adherence before the alteration of drug regimen and thereby contributing to enhancement of statin therapy management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
2
8
0
3
Order By: Relevance
“…In our study, full adherence was reported by >80% of all respondents, and only 2.8% of them had <23 points. Similar results were found in another study from the Czech Republic, in which the MARS-CZ was used to determine self-reported adherence to statins 10. Similar findings to ours were also observed with other scales (eg, the Basel Assessment of Adherence with Immunosuppressive Medication Scales), even if a less strict scoring method was used 20,21.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, full adherence was reported by >80% of all respondents, and only 2.8% of them had <23 points. Similar results were found in another study from the Czech Republic, in which the MARS-CZ was used to determine self-reported adherence to statins 10. Similar findings to ours were also observed with other scales (eg, the Basel Assessment of Adherence with Immunosuppressive Medication Scales), even if a less strict scoring method was used 20,21.…”
Section: Discussionsupporting
confidence: 89%
“…Patients were also asked to rate their health status using the 5-point Likert scale. Self-reported medication adherence was measured by the Czech version of the Medication Adherence Report Scale (MARS-CZ), which was validated in an interview 10. The MARS-CZ can be employed in various diseases with similar dosing regimen, as the items are focused on the patients’ intentional or unintentional changes in prescribed dosages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a generic tool, which can be administered regardless of the disease and the prescribed drug. It has been validated so far in different clinical settings, namely statin therapy [15], rheumatoid arthritis [16], asthma [17], psychosis [18], and has been used for assessing adherence in many clinical studies worldwide [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Despite anonymity of the respondent, self-reported quantitative compliance (questions on doses used or missed) was almost always very high. 15 , 30 32 Social desirability is probably the dominant reason why our participants not only overrated their compliance by the questionnaire, but also spilled tablets out of MEMS and returned empty containers in most cases. Hawthorne effect refers to those patients who overestimate their adherence when they know they are monitored.…”
Section: Discussionmentioning
confidence: 92%